The Valorization of Communicative Event as a Text-formation Factor (based on Osip Bodansky’s diary of the period 1852-1857) - Radziievska Tetiana (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2020)

(untitled)
The object of the study is the diary records of the well-known Slavist of the XIXth century Osip Bod’ansky, which are examined in the perspective of pragmalinguistics and text-formation in diary discourse. It is shown that syntax and semantics of O. Bod’ansky’s diary records have some peculiarities correlating with the diarist’s intention and the major text-formation factor deals here with the valorization of a speech event. In this case diary text focuses on the detailed representation of the speech events of different types.Based on data from the whole corpus of published records of the period 1852-1857, the study aims to demonstrate that the specificity of Bod’ansky’s diary is determined by selection of events: the exclusion of the information on personal events and the inclusion of the information on speech events which is regarded by him as relevant and significant. The content of the records covers both dialogue speech events and monologue ones (stories, news, pieces of information, anecdotes, jokes, rumors, quotations etc.). Syntax of the sentences is represented by complicated hierarchical syntactical structures which combine various excerpts of direct and indirect speech, remarks with speech act predicates, embedded phrases. The sentences here are saturated with chains of syntactical components with the function to identify a person, a place, an object, a day of the week, a book, a building, to give more precise or extra information about the speech events. Some of these constructions or word-combinations are formed as parenthesis. The analysis allowed to conclude that in the textual activity, which is represented by Bod’ansky’s diary, the valorization of a communicative event logically correlates with the main intentional component of this activity, dealing with the purpose to document the information on the event as a whole. So the diary texts in this case are characterized by high informative density.